New Technologies for the Preservation, Conservation and Enhancement of Verona’s UNESCO Heritage: The Walls - Becherini, Pietro (Restauro Archeologico, 2023)
The Veronese fortified site, a UNESCO heritage site, has in recent years been the subject of important digital documentation, unique in the Verona area. The research was an opportunity to verify a process whose technological developments in the field of heritage documentation have offered significant opportunities for the survey of architecture both in the metric data acquisition phase and in representation and dissemination. The study is part of the research project "Verona Fortificata", born in 2015 thanks to the collaboration between the Universities of Florence and Pavia and the Municipality of Verona. The aim is to focus on what has been obtained from a sort of "resulting product" of the classical survey and the consequent possibility of its use to provide preliminary but essential data for the Municipality's assessment of the actual Buffer Zone of the UNESCO site, of the visual impact of both the monument and the extraneous elements that are nevertheless part of the context.